The efficacy of branched-chain amino acid granules to restore phagocytic activity in cirrhosis patients, a randomized controlled trial - Chamroonkul, Naichaya; Rujeerapaiboon, Natthapat; Sripongpun, Pimsiri; Kaewdech, Apichat; Piratvisuth, Teerha (Frontiers in Nutrition, 2023)
Background Infection is a detrimental complication among cirrhotic patients, leading to major morbidity and mortality. Reduction in phagocytic activation, as part of immunoparesis, is a distinctive key component of cirrhosis-associated immune dysfunction (CAID) and predicts the development of infection. However, there are limited data on immunotherapeutic approaches to restore phagocytosis. Aims We aimed to determine the effect of branched-chain amino acid (BCAA) granules on phagocytic activity in patients with CAID. Method In this double-blind randomised controlled trial, Participants were randomly assigned (1:1 ratio stratified by Child-Pugh status) to receive either BCAA granules or placebo. In the 3rd and 6th months, phagocytic activity was assessed by flow cytometry. The primary endpoint was the restoration of innate immunity at the 6th month, defined as ≥75% phagocytic activity; the secondary endpoints were the accretion of phagocytic activity and hospitalization due to infection. Results A total of 37 patients were included. There were no differences among the patients in the baseline characteristics and phagocytic activity. At the 6th month, a higher proportion of patients with phagocytic restoration was observed in the BCAA granule group compared to the placebo group (68% vs. 5.6%, p<0.001). The mean phagocytic activity was 75.4% and 63.4% in the BCAA granule and placebo groups, respectively (p<0.001). Progressive accretion of phagocytic activity was observed during the 3rd and 6th months. There was no difference in hospitalization due to infection (3 vs. 2 events, p=0.487). Conclusion Our results suggest that BCAA granules significantly restore phagocytic activity across various stages of cirrhosis. A longer follow-up period is required to demonstrate infection prevention.